Genome-Wide Association Study Identifies Novel Colony Stimulating Factor 1 Locus Conferring Susceptibility to Cryptococcosis in Human Immunodeficiency Virus-Infected South Africans. (16th October 2020) - Kannambath, Shichina; Jarvis, Joseph N; Wake, Rachel M; Longley, Nicky; Loyse, Angela; Matzaraki, Vicky; Aguirre-Gamboa, Raúl; Wijmenga, Cisca; Doyle, Ronan; Paximadis, Maria; Tiemessen, Caroline T; Kumar, Vinod; et al.
Abstract: Background: Cryptococcus is the most common cause of meningitis in human immunodeficiency virus (HIV)-infected Africans. Despite universal exposure, only 5%–10% of patients with HIV/acquired immune deficiency syndrome and profound CD4 + T-cell depletion develop disseminated cryptococcosis: host genetic factors may play a role. Prior targeted immunogenetic studies in cryptococcosis have comprised few Africans. Methods: We analyzed genome-wide single-nucleotide polymorphism (SNP) genotype data from 524 patients of African descent: 243 cases (advanced HIV with cryptococcal antigenemia and/or cryptococcal meningitis) and 281 controls (advanced HIV, no history of cryptococcosis, negative serum cryptococcal antigen). Results: Six loci upstream of the colony-stimulating factor 1 ( CSF1 ) gene, encoding macrophage colony-stimulating factor (M-CSF) were associated with susceptibility to cryptococcosis at P < 10 –6 and remained significantly associated in a second South African cohort (83 cases; 128 controls). Meta-analysis of the genotyped CSF1 SNP rs1999713 showed an odds ratio for cryptococcosis susceptibility of 0.53 (95% confidence interval, 0.42–0.66; P = 5.96 × 10 −8 ). Ex vivo functional validation and transcriptomic studies confirmed the importance of macrophage activation by M-CSF in host defence against Cryptococcus in HIV-infected patients and healthy, ethnically matched controls. Conclusions: This first genome-wide association study of susceptibility to cryptococcosis has identified novel and immunologically relevant susceptibility loci, which may help define novel strategies for prevention or immunotherapy of HIV-associated cryptococcal meningitis. Abstract : In this first GWAS conducted in cryptococcosis, we describe, replicate and functionally validate novel loci upstream of the colony stimulating factor 1 (CSF1) gene encoding macrophage colony-stimulating factor (M-CSF) as associated with susceptibility to cryptococcosis in HIV-infected South Africans.